Review and analysis of vulnerability to rainfall variability and policy responses to agricultural water supply in Nigeria (2016)
This paper reviewed and analysed vulnerability to climate change-induced rainfall variability and policy responses to agricultural water supply in Nigeria. The review provides evidence for policy feedbacks as well as priority setting for the post-2015 sustainable development agenda. Nigeria’s vulnerability to climate change variability is due to a number of factors: its geographical characteristics, limited capacity to adapt, dependence on climate-sensitive resources, teeming population, and concentration of Gross Domestic Product (GDP) generating industries in locations that are highly vulnerable to climate change. The poverty level in the country could further worsen climate change adaptation and mitigation strategies. The policy responses were identified and categorized either as climate change sensitive or climatic change specific.